FEMINIZE THE University? A commitment to complementarity - Redondo Redondo, María Lourdes (2020)
The article aims to show that the University, in its identity and mission, has an essential feminine component. University is a feminine word, as it is "wisdom", "education" and "alma mater", pillars of a humanist University, today in crisis due to the predominance of a masculine model of knowledge (activist, technical and competitive). The feminine and the masculine are two complementary ways of being that permeate everything human and, consequently, the University. In the current moment of denial and confusion of identities, it is necessary to discover, strengthen and harmonize the masculine and the feminine in all fields and, in particular, the university, "the soul of civilization", because it is where power ideas born. This work is limited to "the feminine", waiting for another to complement it. The basis is a "dual anthropology", the only one capable of explaining the human and, therefore, the university.